MARVEL SPIDERMAN : SHORT CIRCUIT (Cottage Farm, United Kingdom : Autumn Publishing, 2021)
Prepare for the ultimate storytime with the amazing Spider-Man and his friends as they battle evil and protect New York City.
A shocking tale of action, adventure and Super Hero Fun.
Keywords: Readers; Fiction